Patients' perceptions and understanding of informed consent for surgical procedures - Kalala, Tshimanga Willy (My University, 2011)
Background Informed consent is required for any surgical procedure. It is a demonstration of a patient‟s agreement to have surgery performed. Many studies have considered the quality of informed consent in clinical trials. However, only few studies have assessed patients‟ understanding of the process of informed consent in clinical practice. This descriptive cross-sectional study has looked at patients‟ perceptions and understanding of informed consent process for surgical procedures. Aim To explore patients‟ perceptions on informed consent and ascertain if those who have signed for surgical procedures have adequate understanding of the informed consent process. Objectives 1. To ascertain patients‟ perceptions of the process of informed consent; 2. To determine patients‟ recollection of elements of this process that were considered when they signed the consent. 5 3. To explore if patients understand the meaning and implications of the informed consent process; 4. To determine whether patients obtained information about procedures from sources other than the healthcare workers; Methods This was a descriptive cross-sectional study conducted among patients admitted at Leratong hospital for elective surgery. A sample of patients (n=98) selected from those booked for elective surgery at Leratong theatres between April 2008 and June 2008 were interviewed. Different aspects of information were analysed. Specifically: social and demographic profile, formal education, previous medical and surgical history, perceptions of informed consent, process of informed consent and knowledge of the procedure‟s indication, risks and alternatives. Equally considered were sources and value of external medical information. Results Patients interviewed represented 5.5% of the total of those booked for elective surgery. The median similar to the modal age was 38 years, 58.2% being females. Only 4.1% had tertiary education, 32% did not reach secondary school of which 11.2% had no formal education at all. Concerning their prior medical /surgical background, 26.5% were on chronic medical treatment and 48% had previous surgery. More than two third (91%) of them had stayed in the hospital for more than 12 hours prior to surgery. 6 Only 27% perceived the signing of consent form as a proof that they understood the procedure. It was demonstrated that the higher the education level the better the perceptions of informed consent process (P=0.0006). More than 2/3 of patients needed further explanation in their mother tongue to understand the information. Seventy-four per cent did not read the consent form. The understanding of information was more likely to be checked when the information was given by a doctor than by a nursing sister (P=0.014). Only 8% admitted to know some alternatives to the proposed procedure, 13% of patients knew the risks. Formal education was not linked to better understanding of the informed consent process (P=0.245). Patients claiming to have received further information on the procedure from sources other than the healthcare system did not show an added advantage on understanding (P=0.152). The study has demonstrated the low level of understanding of informed consent process in this provincial public hospital. It has shown the public perceptions of the consent form, and the advantage granted by the formal education in this regards. Based on these results, it is therefore recommended that an approved translation of the consent form be made available to patients as an alternative to those who are not English speakers. A proper guideline should be established for physicians to ensure disclosure of information in language of choice of patients to obtain better informed consent.
MMed, Family Medicine, University of the Witwatersrand, 2011
Keywords: patients understanding; informed consent; surgical procedures